High rate of conversion from ocular hypertension to glaucoma in subjects with uveitis - Ma, Tiffany; Sims, Joanne L; Bennett, Sonya; Chew, Shenton; Niederer, Rachael L (British journal of ophthalmology, 2022)
AimsTo examine presentation, management and long-term sequelae of ocular hypertension and uveitic glaucoma.MethodsRetrospective observational study of all subjects with uveitic glaucoma or ocular hypertension seen in Auckland uveitis clinics over the last 10 years.ResultsA total of 188 eyes of 139 subjects with uveitic glaucoma or ocular hypertension were included for analysis. Total follow-up was 1854.5 eye years (mean 9.9 years). The mean age at uveitis diagnosis was 49.3 years. 52.5% of subjects were male. The most common diagnoses were idiopathic uveitis (29.3%), sarcoidosis (13.3%), herpes zoster (6.9%), HLA-B27 uveitis (6.9%), tuberculosis (5.9%) and Posner-Schlossmann or cytomegalovirus (CMV) uveitis (5.3%). Median intraocular pressure (IOP) at diagnosis was 35 mm Hg (IQR 29–45). 144 eyes (77.0%) developed glaucoma during the follow-up period, of whom 41 lost some central vision due to glaucoma. Oral acetazolamide was required for IOP control in 64.5%, 50 eyes underwent trabeculectomy, 18 eyes required a tube and 6 underwent minimally invasive glaucoma surgery.ConclusionRapid progression was observed from ocular hypertension to uveitic glaucoma. Uveitic glaucoma is aggressive, with high likelihood of requiring surgical management and high risk of central vision loss. Close collaboration between uveitis and glaucoma specialists is required to maximise outcomes for these patients.